Metode kepemimpinan Generasi Z yang Ideal dalam Lingkungan Organisasi - Danang Nugroho; Nia Wirahma Arti; Putri Juwita; Wiwit Fauziah; Zahra Nuril Azizah; Zulfa Alwina (CV. KAMPUS AKADEMIK PUBLISING, 2024)
The digital era has given birth to Generation Z, a generation that was born in the internet era and has unique characteristics. Understanding the ideal leadership style for Generation Z in an organizational environment is crucial for the organization’s future success. This research analyzes the transformative leadership style as the ideal leadership style for Generation Z, based on an in-depth literature study.